"Greener" and modular synthesis of triazine-based conjugated porous polymers via direct arylation polymerization: structure–function relationship and photocatalytic application. Issue 15 (22nd March 2018) - Bohra, Hassan; Li, Peizhou; Yang, Cangjie; Zhao, Yanli; Wang, Mingfeng
Abstract : Triazine-based conjugated porous polymers were synthesised by direct arylation polymerization and used as photocatalysts for aerobic oxidation of benzylamine. Abstract : Triazine-containing conjugated porous polymers (CPPs) as a type of nitrogen-rich optoelectronic material have been promising for versatile applications such as gas separation, energy storage and catalysis. However, previous synthetic approaches such as the ionothermal and solvothermal cyclotrimerization of aryl nitriles to these CPPs are limited to monomers that are stable against high temperatures (≥ 400 °C) or strong acids. As a consequence, a more generally applicable synthetic strategy under milder reaction conditions is highly demanded. In this article, we report direct arylation polymerization (DAP) towards such a synthetic strategy for a new series of robust triazine-core polymers by coupling 2, 4, 6-(tri-2-thienyl)-1, 3, 5-triazine (TTT ) with multi-brominated monomers of varying geometries, without need for pre-activating the C–H bonds in the arene monomers. The direct C–H activation ofTTT enables the facile incorporation of the triazine unit into multidimensional polymeric structures while the choice of comonomers gives good synthetic control of the morphologies, porosities and optoelectronic properties of triazine-core CPPs. The resulting triazine-core polymers were used to catalyze the photo-oxidation of benzylamines and the polymers containing the highest fraction of triazine units showed > 99% conversion with a relatively low loading of the catalyst.